2020
DOI: 10.3390/jcm9072317
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Dry Powder Antibiotics in Patients with Non-Cystic Fibrosis Bronchiectasis: Efficacy and Safety in a Real-Life Study

Abstract: Background: Nebulised antibiotics are habitually used in patients with bronchiectasis, but the use of dry powder inhaled antibiotics (DPIA) in these patients is extremely limited. This study seeks to analyse the efficacy and safety of DPIA in bronchiectasis patients. Material and methods: Multi-centre study of historic cohorts. All the hospital centres in Spain were contacted in order to collect data on patients with a diagnosis of bronchiectasis who had taken at least one dose of DPIA. Its efficacy was analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…Study-related cough was reported as an adverse event in 25% of subjects with DPI versus 4% of the subjects on SVN [ 33 ], although in most cases this did not require medication withdrawal. In a real-world study performed in 164 NCFB patients, who were treated with colistin or tobramycin via DPI [ 7 ], 24.4% of them were withdrawn from treatment, mainly due to cough. Main risk factors were previous coughing, COPD and insufficient patient instruction regarding how to use the device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study-related cough was reported as an adverse event in 25% of subjects with DPI versus 4% of the subjects on SVN [ 33 ], although in most cases this did not require medication withdrawal. In a real-world study performed in 164 NCFB patients, who were treated with colistin or tobramycin via DPI [ 7 ], 24.4% of them were withdrawn from treatment, mainly due to cough. Main risk factors were previous coughing, COPD and insufficient patient instruction regarding how to use the device.…”
Section: Discussionmentioning
confidence: 99%
“…Devices used to deliver therapeutic agents as aerosols are based on nebulizers (SVN), pressurized metered-dose inhalers, or dry powder inhalers (DPI) [ 7 ], mostly for beta-agonists, anti-cholinergic agents, and steroids [ 8 ]. Clinical insight suggests that not only different types of devices, but even different models of the same device, can make a difference on efficiency [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Martínez-García et al study concluded there was no difference in endpoints between colistin and tobramycin [14]. In their analysis, they found that the use of any inhaled antibiotic was beneficial for the patients as it resulted in a marked decline in long-standing bronchial infection.…”
Section: Efficacy and Usementioning
confidence: 97%
“…It is worth mentioning that the efficacy and safety profile of a drug can vary depending on the form of atomizer being used. In order to make a better understanding of the available treatment options, we made a comparison of the drugs in accordance to the type of inhalation form used [14][15][16][17][18][19][20][21].…”
Section: Safety Profile and Concernsmentioning
confidence: 99%
See 1 more Smart Citation